PENGARUH WORKPLACE SPIRITUALITY TERHADAP EMPLOYEE CREATIVITY DI MEDIASI INTRINSIC MOTIVATION DAN PSYCHOLOGICAL EMPOWERMENT PADA INDUSTRI ASURANSI DI MASA PANDEMIC COVID 19 - Suciariani; Mutiara Sibarani Panggabean (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study is to analyze the influence of Workplace Sprirituality on Employee Creativity through Psychological Empowerment and Intrinsic Motivation in the South Jakarta Insurance Industry. The data collection technique uses a questionnaire directly where the data is spread using an online questionnaire using a google form. The results of the questionnaire obtained a total sample of 290 respondents of Human Resources employees who worked for 4 (Four) life insurance in the South Jakarta Region. The analysis method used in this study is SEM (Structural Equation Modelling) analysis using the help of AMOS (Analysis of Moment Structure) software. The results showed that there is a negative influence of workplace spirituality on employee creativity, there is a negative influence of intrinsic motivation on employee creativity, there is a positive influence of psychological empowerment on employee creativity.